Inheritance of the resistance to phaeosphaeria leaf spot in maize - Pegoraro, Diego Girardi; Neto, José Fernandes Barbosa; Soglio, Fábio Kessler Dal; Vacaro, Elton; Nuss, Claudio Natalino; Conceição, Léo Duc Haa (Pesquisa Agropecuaria Brasileira, 2002)
Phaeosphaeria leaf spot (PLS) has caused an expressive reduction in the corn grain yield in Brazil. The increment in sowing date amplitude, conjugated with the use of irrigated areas and zero tillage, had major contribution in the increase of phaeosphaeria leaf spot (PLS) incidence and severity. For this reason, it is important to develop resistant genotypes to this disease; however, an efficient selection depends upon the understanding of the genetic variability and inheritance of the resistance. Aiming to determine combining ability and the mode of inheritance for PLS, seven corn inbreds were crossed for diallel and generation mean analysis. The experiments were conducted in Xanxerê, SC. Percentage of foliar area affected by the disease was evaluated 30 days after flowering. The genotypes presented amplitude of 4.3% to 67.0% of foliar area affected by PLS. The LA06 and its hybrids showed high level of resistance. Results indicated that selection for PLS resistant genotypes could be successfully accomplished in corn breeding programs. At least two major independent genes were identified with a preponderant participation of addictive effects in the inheritance of the trait.